European Funds and Investment Attractiveness of Polish Poviats. Analysis of Spatial Relationships - Laskowska, Iwona; Dańska-Borsiak, Barbara (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
One of the basic tools of the EU cohesion policy are the European Funds. These funds are directed on activities strengthening the competitiveness of economies and increasing investment attractiveness of regions. The attractiveness is understood as the ability to attract investors to the region due to the location benefits being offered. The EU Funds are of particular importance for strengthening the factors that contribute to improving the investment attractiveness of regions or weakening the existing barriers. This study attempts to assess the relationship between the amount of support obtained from the European Funds and the investment attractiveness of Polish regions. The research was carried out at the level of poviats (NUTS–4), which allows for a fairly precise assessment of the territorial differentiation of the investment attractiveness of the country. The main objective of the study was to assess the impact of European funds raised by poviats on their investment attractiveness, while taking into account spatial dependencies. The additional objectives were: to determine the level of investment attractiveness of poviats on the basis of selected partial measures and to construct a composite measure of investment attractiveness. The analysis of spatial dependencies has additionally allowed to determine the spatial pattern of poviats investment attractiveness and identification of the centres affecting positively or negatively the neighbouring regions. The research proved the existence of significant differences in the level of investment attractiveness of poviats (the most attractive ones are the city‑poviats of: Warszawa, Sopot, Krakow, Katowice and Świnoujście). The results of spatial models indicate that a significant, positive impact on the level of poviat’s investment attractiveness is exerted not only by the use of European Funds in the poviat, but also the absorption of these funds in neighboring poviats.